Kyrgyz Republic improving growth potential. - Yamano, Takashi (Country diagnostic studies, 2019)
The Kyrgyz Republic has overcome some complex challenges to now have one of the most open economies in Central Asia. The country has improved its per capita income and living standards and is on the threshold of becoming a lower-middle-income economy. Looking ahead, the main challenge for the Kyrgyz Republic is to build on these successes to stimulate stronger, more broad-based economic growth. This book identifies the economic and governance reforms needed within key sectors to drive this growth. It provides policy suggestions to enhance the countrys trade, agriculture, tourism, finance, information and communications technology, energy, transport and logistics, and human capital.